The developing juvenile distal tibia: Radiographic identification of distinct ontogenetic phases and structural trajectories. Issue 2 (11th October 2022) - Reid, Rebecca A. G.; Davies, Catriona; Cunningham, Craig
Abstract: A novel combination of radiographic colour gradient mapping and radiographic absorptiometry was utilised to examine 96 human distal tibiae from 54 individuals ranging in age‐at‐death from the foetal to 23 years. The purpose of this was to identify previously undocumented changes in the internal organisation during the development of the distal tibia and determine whether these changes could be described as distinct phases. Previous studies have demonstrated a rudimentary structural organisation in other skeletal elements that mirror more mature patterns of bone organisation. Results showed that the perinatal tibia did not exhibit a rudimentary structural pattern similar to the architecture observed within the late adolescent tibia. This lack of early internal organisation is hypothesised to be related to the rudimentary ossification process that is being laid down around a pre‐existing vascular template which will be subsequently modified by locomotive forces. Between birth and 2 years of age, the tibia exhibited a period of regression where radiodensity decreased in comparison to the perinatal tibia. This period of regression was postulated to be due to a combination of factors including changing locomotive forces, weaning and growth resulting in a stage of development which is extremely demanding on calcium liberation from the skeleton. After 2 years of age, the distal tibia demonstrated refinement where radiographic trajectories progressively developed into patterns consistent with adult trabecular organisation. These trajectories are linked to the forces associated with the bipedal gait, suggesting a strong influence of biomechanical forces on the development of the distal tibia. Abstract : xxxx